Health Literacy and Use of Preventative Care of Female Undergraduate Nursing vs. Non-Nursing Students (International Journal of Studies in Nursing, 2017)
Background: Health literacy and use of preventative care are important aspects of health care. Health literacy, or the ability to understand basic medical knowledge, affects a person’s understanding and use of preventative health care. Aim: This study was designed to investigate the perception of health literacy and use of preventative care resources by female undergraduate college students. Method: This is a quantitative, non-experimental descriptive research study with a cross-sectional design. A 30-item demographic yes or no and a Likert-type scale was used to survey 62 female college students living in a dormitory. The goal was to discover if additional education is needed to obtain optimal utilization of health care resources for this population. Result: Surveying the undergraduate nursing and non-nursing students helped raise awareness of health literacy of the female students. Conclusion: Understanding the use of preventative care resources by this population may influence the way nursing interventions are formulated.